2018
DOI: 10.1097/md.0000000000012013
|View full text |Cite
|
Sign up to set email alerts
|

Morning hypertension is a risk factor of macrovascular events following cerebral infarction

Abstract: This study aimed to investigate risk factors (such as morning hypertension, drug compliance, and biochemical parameters) of macrovascular events after cerebral infarction.This was a retrospective study of patients with cerebral infarction admitted between May 2015 and April 2016 at the Fengxian Branch, 6th People's Hospital of Shanghai. They were divided into the macrovascular events and control groups according to the diagnosis of macrovascular events following cerebral infarction.Among the 702 patients inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
(42 reference statements)
0
4
2
1
Order By: Relevance
“…In the MoHT group, the multivariable analysis showed that a history of previous cardiovascular disease was the signifcantly independent associated factor. Even though the previous evidence supported that morning hypertension was strongly related to stroke [9,34,35], It could not show the causal efect of cardiovascular disease and MoHT in this study because of the limitation of the cross-sectional design. For EHT and MoEHT groups, the independently associated clinical factor was taking at least 1 long-acting antihypertensive drug once daily in the morning.…”
Section: Discussioncontrasting
confidence: 63%
“…In the MoHT group, the multivariable analysis showed that a history of previous cardiovascular disease was the signifcantly independent associated factor. Even though the previous evidence supported that morning hypertension was strongly related to stroke [9,34,35], It could not show the causal efect of cardiovascular disease and MoHT in this study because of the limitation of the cross-sectional design. For EHT and MoEHT groups, the independently associated clinical factor was taking at least 1 long-acting antihypertensive drug once daily in the morning.…”
Section: Discussioncontrasting
confidence: 63%
“…In this study, the detection rate of dyslipidemia in the high-risk population, lower only than that of hypertension, was 64.5%, indicating the key role of dyslipidemia in increasing the risk of stroke. Studies showed that patients with dyslipidemia were at an increased risk of hemorrhagic stroke (26), and the administration of statins was an independent protective factor against macrovascular events (27). Diabetes is an independent risk factor for stroke, and the stroke exposure rate of people with diabetes is 1.5-3.0 times that of non-diabetic people (28).…”
Section: Discussionmentioning
confidence: 99%
“…среди не достигших целевого аД преобладали лица с профилем «Non-dipper», среди достигших -«Dipper», хотя статистически значимой разницы получено не было. Более высокие показатели вУп аД у пациентов, достигших целевого уровня аД, свидетельствуют о его компенсаторном физиологическом нарастании и отражают эффективность терапии [30,31].…”
Section: ðåçóëüòàòûunclassified